Effect of light on conidiation of nit and lis mutants of Neurospora crassa grown on different nitrogen sources - H. Reimer; H. Ninnemann (Fungal Genetics Reports, 1992)
In addition to a recent paper (Ninnemann 1991. J. Photochem. Photobiol. 9:189-199), we are reporting further data on Neurospora crassa mutants supporting our hypothesis that the flavohemoenzyme nitrate reductase (NR) is involved in photoreception for light- promoted conidiation (Klemm and Ninnemann 1979. Photochem. Photobiol. 29:629-632). We looked for light-stimulated conidiation and NR activities in the NR- regulatory mutants nit-2 (FGSC 2698), nit-4 (2992) and nit-5 (985) from the Fungal Genetics Stock Center, University of Kansas, as well as the four NR+ mutants bd lis-1 (2891), bd lis-2 (2892), bd lis-3 (2983), and al-2 bd, received from Dr. S. Brody, University of California, San Diego. The three "light insensitive" lis mutants were isolated and described by Paietta and Sargent in 1983 (Genetics 104:11-21): the expression of their circadian rhythm was relatively insensitive to continuous light.